Visceral myopathy: Clinical and molecular survey of a cohort of seven new patients and state of the art of overlapping phenotypes. - Moreno, Carolina Araujo; Metze, Konradin; Lomazi, Elizete Aparecida; Bertola, Débora Romeo; Barbosa, Ricardo Henrique Almeida; Cosentino, Viviana; Sobreira, Nara; Cavalcanti, Denise Pontes (Am J Med Genet A, 2016)
Visceral motility dysfunction is a key feature of genetic disorders such as megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS, MIM moved from 249210 to 155310), chronic intestinal pseudo-obstruction (CIPO, MIM609629), and multisystemic smooth muscle dysfunction syndrome (MSMDS, MIM613834). The genetic bases of these conditions recently begun to be clarified with the identification of pathogenic variants in ACTG2, ACTA2, and MYH11 in individuals with visceral motility dysfunction. The MMIHS was associated with the heterozygous variant in ACTG2 and homozygous variant in MYH11, while the heterozygous variant in ACTA2 was observed in patients with MSMDS. In this study, we describe the clinical data as well as the molecular investigation of seven individuals with visceral myopathy phenotypes. Five patients presented with MMIHS, including two siblings from consanguineous parents, one had CIPO, and the other had MSMDS. In three individuals with MMIHS and in one with CIPO we identified heterozygous variant in ACTG2, one being a novel variant (c.584C>T-p.Thr195Ile). In the individual with MSMDS we identified a heterozygous variant in ACTA2. We performed the whole-exome sequencing in one sibling with MMIHS and her parents; however, the pathogenic variant responsible for her phenotype could not be identified. These results reinforce the clinical and genetic heterogeneity of the visceral myopathies. Although many cases of MMIHS are associated with ACTG2 variants, we suggest that other genes, besides MYH11, could cause the MMIHS with autosomal recessive pattern. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Actins; Child, Preschool; Colon; Consanguinity; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Phenotype; Polymorphism, Single Nucleotide; Treatment Outcome; Ultrasonography, Prenatal; Urinary Bladder